PETROGRAPHIC ANALYSES OF COAL DEPOSITS FROM CIGUDEG AND BOJONGMANIK AREAS WITH REGARD TO THEIR UTILISATION - BINARKO SANTOSO; NINING S. NINGRUM (Indonesian Mining Journal, 2008)
Geological setting of the Cigudeg and Bojongmanik areas gives rise to the coal characteristics, par- ticularly due to the depositional environment and stratigraphic aspect. Those characteristics include lithotype, type and rank of the coals. The coals formed under wet-swamp condition to result in brighter lithotype and vitrinite-rich coal. By contrast, the coals formed under dry-swamp condition to result in duller lithotype and inertinite-rich coal. The Cigudeg coals contain clay minerals and quartz, whilst the Bojongmanik coals contain pyrite and calcite. These minerals are beneficial to interpret depositional environment of the coals. Ranks of the Bojongmanik coals are somewhat higher (lignite-subbitumi- nous C-B) that those of the Cigudeg coals (lignite-subbituminous B) according to the ASTM classifi- cation. These higher ranks are due to the thicker overburden on the Bojongmanik coals in terms of stratigraphic aspect. Regarding those petrographic characteristics, both coals are suitable for fuel of direct combustion for the small-scale and home industries that are available in the surrounding areas. Therefore, the coals can economically cope with the demand of those industries.